An honorable assassin - Hamilton, Steve, 1961- (Hamilton, Steve, 1961- Nick Mason novel., 2024)
"He was released from federal prison to a second life as an unwilling assassin, serving a major Chicago crime lord until the day he finally won his freedom. But that freedom was a lie. Now Mason finds himself on a plane to Jakarta, promoted to lead assassin for a vast shadow organization that reaches every corner of the globe. This time, there's only one name on his list: Hashim Baya--otherwise known as the Crocodile--international fugitive and #1 most wanted on Interpol's "Red Notice" list. Baya is the most dangerous and elusive criminal Mason has ever faced. And for the first time in his career, Mason fails his mission. Baya gets away alive. There's only one thing he can do now: to save himself, his ex-wife, and his daughter, he must make this mission his life, hunting down the target on his own. But Mason isn't alone in his search, because for Interpol agent Martin Sauvage, apprehending Baya has become a personal vendetta. Sauvage is a man just as haunted as Mason. And just as determined. Never have the stakes been so high, the forces surrounding him so great. Sauvage wants Baya in prison. Mason needs him in a body bag. Assassin and cop are on a five-thousand-mile collision course, leading to a brutal final showdown--and the one man in the world who can finally show Nick Mason the way to freedom"--Provided by publisher.